Relapsing severe Crohn’s colitis and perianal fistula on Infliximab maintenance therapy - Guha, Abhraneel; Chaurasia, Kundan; Singh, Harsh Deepak; Joshi, Mandeep; Pal, B B (Eastern Journal of Medical Sciences, 2019)
Perianal fistula occurs in up to 43% of patients with Crohn’s disease. In Crohn’s disease it is important to identify the site of inflammation, area involved and based on that the treatment regimen is decided. Perianal abscesses must be drained and perianal fistulas must be treated with surgical and medical management. In this case report we would discuss about a patient who underwent failure with first line treatment and developed fistula. His symptoms decreased with due course of management and was advised for surgical procedure along with medical management.